PENGAWASAN BAGI ORANG ASING YANG OVERSTAY DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2011 TENTANG KEIMIGRASIAN - Mamay Komariah (Kajian Hukum, 2018)
Indonesia has a strategic position in international life, both from the geographical aspect and the potential of natural resources and human resources, resulting in increased traffic flow of people into and out of Indonesia. Foreigners who come to Indonesia and have an immigration permit, can only stay in Indonesia for the time specified in the immigration permit. If a foreigner comes to Indonesia, his immigration permit expires and is still within the territory of Indonesia beyond no more than 60 (sixty) days from the immigration permit granted, is subject to a load, while Foreigners who come to Indonesia, the immigration permit expires and is still within the territory of Indonesia beyond 60 (sixty) days from the deadline then the foreigner will be subject to criminal Article 124 of the Immigration Act Number 6 of 2011, with a maximum imprisonment of 2 (two) years or a maximum fine of Rp. 25,000,000- (twenty five million rupiah). The existence of a foreigner in the territory of Indonesia that exceeds the time limit for a residence permit, which is also known in the immigration field as overstay.Services and supervision in the immigration sector are carried out based on the principle of selective policy. Based on this principle, only foreigners can benefit the welfare of the people, nation and State of the Republic of Indonesia and do not endanger security and order and are not hostile towards the people, nation and the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution which is permitted in and out of Indonesia.Sanctions imposed on foreign nationals who commit immigration violations are Immigration sanctions and law enforcement through Administrative sanctions and Criminal sanctions with the Criminal Justice System. Immigration sanctions are administratively more effective and efficient, in the case of overstay.Keywords : Supervision, Overstay, Act Number 6 Of 2011 Concerning Immigration